Kinetics of binding of fluorescent ligands to enzymes with engineered access tunnels - Kaushik, Shubhangi; Prokop, Zbynek; Damborsky, Jiri; Chaloupkova, Radka (The FEBS journal, 2017)
Molecular recognition mechanisms and kinetics of binding of ligands to buried active sites via access tunnels are not well understood. Fluorescence polarization enables rapid and non-destructive real-time quantification of the association between small fluorescent ligands and large biomolecules. In this study, we describe analysis of binding kinetics of fluorescent ligands resembling linear halogenated alkanes to haloalkane dehalogenases. Dehalogenases possess buried active sites connected to the surrounding solvent by access tunnels. Modification of these tunnels by mutagenesis has emerged as a novel strategy to tailor the enzyme properties. We demonstrate that the fluorescence polarization method can sense differences in binding kinetics originating from even single mutations introduced to the tunnels. The results show, strikingly, that the rate constant of the dehalogenase variants varied across seven orders of magnitude, and the type of ligand used strongly affected the binding kinetics of the enzyme. Furthermore, fluorescence polarization could be applied to cell-free extracts instead of purified proteins, extending the method's application to medium-throughput screening of enzyme variant libraries generated in directed evolution experiments. The method can also provide in-depth kinetic information about the rate-determining step in binding kinetics and reveals the bottlenecks of enzyme accessibility. Assuming availability of appropriate fluorescent ligand, the method could be applied for analysis of accessibility of tunnels and buried active sites of enzymes forming a covalent alkyl-enzyme intermediate during their catalytic cycle, such as α/β-hydrolases containing > 100 000 protein sequences based on the Pfam database.
Keywords: Hydrocarbons, Halogenated; Protein Binding; exprese genu; alkany; Gene Expression; Recombinant Proteins; Biocatalysis; proteinové inženýrství; Kinetics; ligandy; Bacterial Proteins; Solvents; Cloning, Molecular; rozpouštědla; klonování DNA; Ligands; halogenované uhlovodíky; mutageneze cílená; Hydrolases; Escherichia coli; Protein Engineering; Alkanes; Databases, Protein; hydrolasy; fluorescenční polarizace; rychlé screeningové testy; rekombinantní proteiny; Mutagenesis, Site-Directed; vazba proteinů; kinetika; Catalytic Domain; Fluorescence Polarization; High-Throughput Screening Assays; bakteriální proteiny; biokatalýza; databáze proteinů; katalytická doména